Lossless compression of repetitive and non repetitive DNA sequences using A Novel first Art methodology - prasad, V Hari; Kumar, Dr.P V (IJRDO -Journal of Computer Science Engineering, 2015)
Excess accumulation of living organisms in a daily routine Genbank sizes are growing exponentially. Now, a challenge to the real world is that accessing and transmitting t the genetic data through network is a cumbersome task. Hence, a feasible solution is compression!.State of the art existing compression algorithms may work on repetitiveness of the sequences and the results are not bountiful in a comparative study. Here a new methodology is proposed for better compression gain.